2022
DOI: 10.1177/20503121221124685
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of intestinal parasites and associated factors among HIV/AIDS patients on antiretroviral therapy at Bule Hora General Hospital, West Guji, Ethiopia

Abstract: Objective: The study aimed to assess the prevalence of intestinal parasites and associated factors among people living with HIV/AIDS on antiretroviral therapy at Bule Hora General Hospital, West Guji, Oromia, Ethiopia. Introduction: Parasitic infection of the intestinal tract is a major source of disease in patients with HIV, particularly in the tropics, where diarrhea is a common complaint with variable severity. Method: An institution-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“… 14 Protozoan infections are categorized under common prevalent human parasitic infections that result in clinical morbidity and mortality and constitute a global health burden. 15 Most giardiasis- and amoebiasis - infected cases were found to be asymptomatic, and the common risk factors are poor hygiene standards, low socioeconomic conditions, and malnutrition in developing countries. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 Protozoan infections are categorized under common prevalent human parasitic infections that result in clinical morbidity and mortality and constitute a global health burden. 15 Most giardiasis- and amoebiasis - infected cases were found to be asymptomatic, and the common risk factors are poor hygiene standards, low socioeconomic conditions, and malnutrition in developing countries. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…14 Protozoan infections are categorized under common prevalent human parasitic infections that result in clinical morbidity and mortality and constitute a global health burden. 15 Most giardiasis-and amoebiasis-infected cases were found to be asymptomatic, and the common risk factors are poor hygiene standards, low socioeconomic conditions, and malnutrition in developing countries. 16,17 Furthermore, IPIs especially helminths are associated with an increased risk of protein-energy malnutrition, nutritional-related anemias, growth defects in children, and low weight gain during pregnancy and lead to low birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…A structured face-to-face interview questionnaire that had been pre-tested and modi ed after reading various types of literature [11][12][13][14][15][16][17] was used to gather the results. These include sanitary and environmental elements, sociodemographic characteristics, and health-related issues.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Subsequently, the entire smear area was examined with a 10-fold objective; if something unusual was observed, the region was magni ed even further (40x) [17].…”
Section: Laboratory Stool Examinationmentioning
confidence: 99%
“…Diarrhea is one of the most common presenting complaints in HIV-infected patients, where most diarrheal infections are associated with intestinal parasites [ 6 ]. Numerous studies demonstrated that intestinal parasites, such as Cryptosporidium spp., Microsporidia spp., Isospora belli , and Cyclospora cayetenensis , were frequently associated with episodes of severe and often fatal diarrhea in HIV-infected patients [ 7 , 8 , 9 ]. Among these parasites, Entamoeba histolytica , Giardia intestinalis , and Strongyloides stercoralis are documented as the most important cause of diarrhea in immune-compromised patients.…”
Section: Introductionmentioning
confidence: 99%